A2_8 Propeller Hats Do Not Make Good Parachutes - Cheshire, K. J.; Davies, C. T.; Garratley, R.; Moore, J. (Physics Special Topics, 2016)
In this paper we investigate whether a person can survive a fall using only a propeller hat to save them as often depicted in cartoons. We find the propeller requires an angular velocity of 58 rads/s for a person to land at a safe velocity of 7 m/s.